al-Dawr al-'Umani fi khidmat al-lughah al-'Arabiyah - Faris, Walid Fikri; al-Zuhaymi, Sallih ibn Sulayman ibn Sallih; al-Shaybani, Sultan ibn Mubarak Hammad (Masqat, Saltanat'Uman : Dhakirat'Uman, 2015)
Arabic language; Oman; history.
Includes bibliographical references.
Keywords: Arabic language -- Study and teaching -- Oman -- History